HUBUNGAN TINGKAT PENDIDIKAN IBU HAMIL DAN DUKUNGAN SUAMI DENGAN FREKUENSI ANTENATAL CARE PADA IBU NIFAS DI WILAYAH KERJA PUSKESMAS SEDAU TAHUN 2017 - Astin Huriani; Una Zaidah (JURNAL SANGKAREANG MATARAM, 2020)
The indicator used to monitor maternal and neonatal health programs is the percentage of pregnant women who perform at least four visits during pregnancy, Visits of Puskesmas Sedau in 2016 reached 1,201pregnant women or about 93.97% of the projected pregnant women in Sedau Community Health Center Amounting to 1,278 pregnant women. While the target K1 is 95%. So the achievement of K1 does not reach the specified target. For the achievement of K4 Sedau Puskesmas only reached 1266 pregnant women or about 88.11% of the target 90%. This means that K4 in the working area of Sedau Puskesmas still has not reached the target.This research is aimed to find out the correlation between maternal education level and husband support with ANC frequencyamongpostpartum mothers in Sedau Puskesmas working area in 2017.This research is an observational analytic research with cross sectional data retrieval time.The population in this study is the number of postpartum target recorded in the working area of Sedau Puskesmas 2016 that is as many as 1299 people and the number of samples as 94 people taken by Quota sampling.Statistical Test with Contingency Coefficient obtained p = 0,000 <α 0.05 (Significant), it means there is a relationship between the Education Level of respondents with the frequency of ANC in the work area Sedau Puskesmas 2017. Coefficient 0.658, means closeness of the relationship between the Education Level respondents with frequency ANC includes ENOUGH / MEDIUM with POSITIVE direction.Test Result Statistic with Contingency Coefficient obtained p value = 0,000 <α 0,05 (Significant), it means there is relation between Family Support of respondent with frequency of ANC in work area of Sedau Puskesmas 2017. Coefficient value 0,593, mean closeness relation between Family support of respondent with ANC frequencies include ENOUGH / MEDIUM with POSITIVE direction